Intervals as Domain Constructor - Callejas Bedregal, R.; Callejas Bedregal, B.R. (Trends in Computational and Applied Mathematics, 2001)
In this work we use an inteval constructor on posets which when applied to a poset D gives a new poset whose elements are intervals of D.